2009
DOI: 10.1073/pnas.0813366106
|View full text |Cite
|
Sign up to set email alerts
|

The methamphetamine-sensitive circadian oscillator does not employ canonical clock genes

Abstract: The ''master clock'' in the suprachiasmatic nucleus (SCN) of the hypothalamus controls most behavioral, physiological, and molecular circadian rhythms in mammals. However, there are other, still unidentified, circadian oscillators that are able to carry out some SCN functions. Here we show that one of these, the methamphetaminesensitive circadian oscillator (MASCO), which generates behavioral rhythms in the absence of the SCN, is based on an entirely different molecular mechanism. We tested mice lacking, or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 20 publications
1
68
1
Order By: Relevance
“…Additionally, an independent methamphetamine-sensitive circadian oscillator (MASCO) may interact with the SCN to alter behavioral rhythms of mice. Independent of the SCN and of circadian clock function, chronic methamphetamine administration induces activity rhythms with a period close to 24 h (Mohawk et al, 2009;Tataroglu et al, 2006). A recent study from Blum and colleagues indicates that the MASCO is a manifestation of a newly discovered dopaminergic oscillator (Blum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an independent methamphetamine-sensitive circadian oscillator (MASCO) may interact with the SCN to alter behavioral rhythms of mice. Independent of the SCN and of circadian clock function, chronic methamphetamine administration induces activity rhythms with a period close to 24 h (Mohawk et al, 2009;Tataroglu et al, 2006). A recent study from Blum and colleagues indicates that the MASCO is a manifestation of a newly discovered dopaminergic oscillator (Blum et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…20). Recent studies investigating the FEO and MASCO in circadian mutant mice have raised the possibility that these oscillators do not require canonical circadian genes to maintain their rhythmicities (5)(6)(7)(8)(9)(10)(11). In this study, we initially sought to investigate the putative noncanonical nature of the MASCO and FEO, and, surprisingly, found that the canonical Period genes participate in period determination in the MASCO and FEO.…”
Section: Discussionmentioning
confidence: 99%
“…12,13). Because only two paralogs of the Period gene, Per1 and Per2, are necessary to generate circadian rhythms in the SCN, previous studies concluded that the FEO and MASCO are "noncanonical" clocks in part because they are functional in Per1 −/− / Per2 −/− mice (5,6). Although the third Period paralog, Per3, is not usually considered a functional component of circadian clocks, we recently demonstrated that Per3 participates in period determination in certain peripheral circadian oscillators (14,15).…”
mentioning
confidence: 99%
“…This suggests that known clock components either are part of the MASCO or link the MASCO to the regular circadian oscillator (RCO). In favor of the second possibility are the findings that all clock gene mutants having methamphetamine in their drinking water can display rhythmic behavior with a period length of between 25 and 37 h, even when the SCN is surgically removed (156). Therefore, one can hypothesize that some clock components are MASCO: methamphetaminesensitive circadian oscillator involved in coupling the long-period MASCO to the shorter-period RCO to bring the two into resonance.…”
Section: Methamphetamine-sensitive Circadian Oscillator (Masco)mentioning
confidence: 99%